118 SHORT-TERM EFFECTS OF DAPAGLIFLOZIN ON CARDIAC BIOMARKERS, FLUID RETENTION, RENAL AND PULMONARY FUNCTION IN HFREF PATIENTS: NOT AS GOOD AS EXPECTED. (15th December 2022) - Mapelli, Massimo; Capovilla, Maria Teresa; Marongiu, Alessandro; Maranzano, Gaspare; Salvioni, Elisabetta; Mattavelli, Irene; Vignati, Carlo; Gugliandolo, Paola; Mantegazza, Valentina; Garlasché, Anna; Agostoni, Piergiuseppe
Abstract: Background: Sodium-glucose co-transporter-2 inhibitors (SGLT2-i) are currently a standard therapy for patients with heart failure with reduced ejection fraction (HFrEF). Still, their potential benefits on biomarkers, respiratory function parameters and fluid retention have not been extensively studied. Bioimpedance vector analysis (BIVA) has emerged as a new tool capable of assessing congestion, providing an estimate of the total body water and hydration index (HI). BIVA is more accurate than NT-proBNP in detecting peripheral congestion in chronic heart failure and can be used to evaluate the effects of the treatment. This study aims to assess the short-term effects of Dapagliflozin on spirometry, diffusing capacity of the lungs for carbon monoxide (DLCO), cardiac biomarkers, and BIVA. Methods: Stable HF patients (EF <40%, NYHA class II or III) eligible for SGLT2-I therapy according to guidelines underwent standard spirometry, DLCO, BIVA and venous blood sampling at baseline (V0) and after 2-4 weeks of therapy (V1). Results: Patients characteristics (N=32) at baseline are shown in Table 1. None of the patients interrupted the treatment and/or experienced adverse events. After 26±6 days, we observed worsening of renal function (eGFR from 73.1±28.5 mL/min/1.73m 2 to 67.4±27.0 mL/min/1.73m 2, p<0.001) and potassium levels (4.36±0.36 mEq/l vs 4.58±0.57 mEq/l, p= 0.017). There were no significant changes in NT-proBNP levels (1378 [615-2542] ng/l vs 1034 [554-2552] ng/l, p= 0.538). HI, total body water, DLCO and spirometry values did not change. On the contrary, a mild reduction in hsTnI was observed (13.88 [9.24-26.8] ng/l vs 11.58 [7.7-24.2] ng/l). Conclusions: Our study did not detect short-term effects of Dapagliflozin on spirometry values, DLCO, fluid retention and NT-proBNP. As revealed in DAPA-HF trial, a mild worsening of potassium and serum creatinine levels was observed. Taken together, these results suggest that the favourable effects of Dapagliflozin could unfold over a longer period of time. A more extended follow-up and a larger population are needed to confirm these preliminary data. Table 1 Mean ± SD Age (years) 63.5 ± 11.3 Female sex (n, %) 5 (16%) BMI (kg/m 2 ) 26.1 ± 2.8 SBP (mmHg) 117.6 ± 16.2 NYHA II (n, %) 31 (97%) LVEF (%) 31.7 ± 7.7 eGFR (mL/min/1.73m 2 ) 73.05 ± 28.5 Ischemic HF (n, %) 19 (59%) ICD (n, %) 18 (58%) CRT (n, %) 7 (23%) Peak VO2 (ml/min) 1203.7 ± 427.1 VE/VCO2 slope 37.6 ± 10.8 Hypertension (n, %) 19 (61%) Diabetes (n, %) 2 (6%) B-Blocker (n, %) 31 (100%) ACE-i / ARBs (n, %) 2 (6%) ARNI (n, %) 29 (94%) MRA (n, %) 27 (68%) Diuretic (n, %) 21 (87%)